2013
DOI: 10.1017/s1463423612000667
|View full text |Cite
|
Sign up to set email alerts
|

Case management of individuals with long-term conditions by community matrons: report of qualitative findings of a mixed method evaluation

Abstract: A thematic analysis resulted in the identification of four themes: (1) visibility; (2) interpersonal relationships; (3) leadership; and (4) systems/professional boundaries. Patients enjoyed being seen as a whole and family carers appreciated the coordination aspect of the role. Difficulties arose from the limited understanding of the CM role and from a lack of a shared vision across healthcare professionals concerning the role and its goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…The literature has explicitly reported that advisors, advocates, carers, communicators, co‐ordinators, educators, facilitators, liaison officers, navigators, negotiators, problem solvers and supporters are roles of case managers working in different care settings (Applebaum & Austin , Saulo , Frankel & Heft‐LaPorte , Abdallah , Mallick , NCMN , Randall et al . , Parker & Fuller ). Our study confirmed that these are also roles of case managers working in the community aged care sector.…”
Section: Discussionmentioning
confidence: 98%
“…The literature has explicitly reported that advisors, advocates, carers, communicators, co‐ordinators, educators, facilitators, liaison officers, navigators, negotiators, problem solvers and supporters are roles of case managers working in different care settings (Applebaum & Austin , Saulo , Frankel & Heft‐LaPorte , Abdallah , Mallick , NCMN , Randall et al . , Parker & Fuller ). Our study confirmed that these are also roles of case managers working in the community aged care sector.…”
Section: Discussionmentioning
confidence: 98%
“…Service models to facilitate access to healthcare for frail older people include care coordination, case management, care navigation, and integrated care, with variable effects on outcomes such as satisfaction, health status, healthcare utilisation or place of death. [13][14][15][16][17][18][19] What these interventions share is their mediation by health or social care professionals working within formal care networks, often with a relatively narrow focus. It may be that service models that sit outside these formal care networks could offer a flexible, innovative, community focused solutions to improving access to care for those who may not usually access palliative or hospice care services, meet needs and enable improved quality of life.…”
Section: Implications For the Publicmentioning
confidence: 99%
“…1 A number of strategies to reduce the burden of long-term illnesses have been driving forward innovations across the UK. Examples of these include the Expert Patients Programmes, 2 the use of community matrons, 3 and the use of Telehealth and Telecare to assess, diagnose, and monitor conditions at home or at a distance from a health and social care provider. [4][5][6] ebb and flow of care for patients, carers, and clinicians.…”
Section: Introductionmentioning
confidence: 99%